2005
DOI: 10.1292/jvms.67.303
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamo-Pituitary-Adrenal Gland Axis in Mice Inhaling Toluene Prior to Low-Level Long-Term Exposure to Formaldehyde

Abstract: ABSTRACT. We studied the change in the hypothalamo-pituitary-adrenal gland (HPA) axis upon adding prior toluene inhalation to our previous formaldehyde inhalation experiments to determine whether short term exposure to relatively high levels of toluene triggers multiple chemical sensitivity (MCS). Data come from immunocytochemical, morphometrical and RT-PCR measurements. Four groups of adult female mice were exposed to differing concentrations (0, 80, 400, and 2,000 ppb) of formaldehyde for 16 hr/day, 5 days/w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Another study also showed an expansion of cells expressing Pomc mRNA (as analyzed by in situ hybridization) 2-3 h after applying a cold stressor in rats (84). Exposure to chemical stressors (such as formaldehyde) also results in a rise of ACTH + cell proportion as analyzed in mice (85). Following exposure of rats to increased ambient temperature, ACTH + cells show reduced volume density, likely due to elevated secretion of ACTH from the corticotrope cells, which is concordant with the higher levels of ACTH (and corticosterone) found in the circulation (86).…”
Section: Pituitary Stem Cells During Physio-pathological Conditions Pituitary Stem Cells During Stressmentioning
confidence: 89%
“…Another study also showed an expansion of cells expressing Pomc mRNA (as analyzed by in situ hybridization) 2-3 h after applying a cold stressor in rats (84). Exposure to chemical stressors (such as formaldehyde) also results in a rise of ACTH + cell proportion as analyzed in mice (85). Following exposure of rats to increased ambient temperature, ACTH + cells show reduced volume density, likely due to elevated secretion of ACTH from the corticotrope cells, which is concordant with the higher levels of ACTH (and corticosterone) found in the circulation (86).…”
Section: Pituitary Stem Cells During Physio-pathological Conditions Pituitary Stem Cells During Stressmentioning
confidence: 89%
“…The toluene inhalation experiment consisted of two related studies. To mimic the preinhalation trigger produced by high-dose toluene, mice were exposed to 500 ppm toluene for three consecutive days prior to FA inhalation [32]. After the three days, groups of mice were exposed to various doses of (0, 80, 400, and 2000 ppb) FA as before [33].…”
Section: Estimation Of the Effect Of Fa And Toluene Inhalation On mentioning
confidence: 99%
“…As toluene is so widely used, the risk of being exposed to it continues to increase both indoors and outdoors (Arlien‐Soborg et al ., 1992). The central nervous system (CNS) has been characterized as the primary target of toluene, in cases of both acute and chronic exposure (Ahmed et al ., 2007; Sari et al ., 2005; Win‐Shwe et al ., 2007); however, there are few reports on the influence of toluene on naive cells in the immune system.…”
Section: Introductionmentioning
confidence: 99%